Living ethics: a stance and its implications in health ethics - Racine, E; Ji, S; Badro, V; Bogossian, A; Bourque, CJ; Bouthillier, M; Chenel, V; Dallaire, C; Doucet, H; Favron-Godbout, C; Fortin, M; Ganache, I; et al. (Springer, 2024)
Moral or ethical questions are vital because they affect our daily lives: what is the best choice we can make, the best action to take in a given situation, and ultimately, the best way to live our lives? Health ethics has contributed to moving ethics toward a more experience-based and user-oriented theoretical and methodological stance but remains in our practice an incomplete lever for human development and flourishing. This context led us to envision and develop the stance of a “living ethics”, described in this inaugural collective and programmatic paper as an effort to consolidate creative collaboration between a wide array of stakeholders. We engaged in a participatory discussion and collective writing process known as instrumentalist concept analysis. This process included initial local consultations, an exploratory literature review, the constitution of a working group of 21 co-authors, and 8 workshops supporting a collaborative thinking and writing process. First, a living ethics designates a stance attentive to human experience and the role played by morality in human existence. Second, a living ethics represents an ongoing effort to interrogate and scrutinize our moral experiences to facilitate adaptation of people and contexts. It promotes the active and inclusive engagement of both individuals and communities in envisioning and enacting scenarios which correspond to their flourishing as authentic ethical agents. Living ethics encourages meaningful participation of stakeholders because moral questions touch deeply upon who we are and who we want to be. We explain various aspects of a living ethics stance, including its theoretical, methodological, and practical implications as well as some barriers to its enactment based on the reflections resulting from the collaborative thinking and writing process.